Some Assembly Required - Sorkin, Michael, 1948-2020 (Book collections on Project MUSE., 2001)
Michael Sorkin is widely hailed as one of the best architecture critics writing today. Iconoclastic and often controversial, he is a witty, entertaining, yet ultimately serious writer. In this new collection, Sorkin reviews the state of contemporary architecture and surveys the dramatic changes in the urban environment of the past decade. From New York to New Delhi, from Shanghai to Cairo, Sorkin offers a sweeping assessment of the impact of globalization, environmental degradation, electronic media, rapid growth, and the legacies of modernist planning.